School-Based Healthy Plate Education and Its Effect on Improving Nutritional Knowledge Among Primary School Students: Edukasi Piring Sehat Berbasis Sekolah terhadap Peningkatan Pengetahuan Gizi Siswa Sekolah Dasar - Kismiasih Adethia; Erin Padilla Siregar; Marliani Marliani; Amelia Erawaty Siregar; Diah Pitaloka; Titis Jernih Wati Gea (Room of Civil Society Development, 2026)
Nutritional problems among primary school children remain a significant public health concern, particularly in the context of the dual burden of malnutrition. This study aimed to examine changes in students’ nutritional knowledge following a school-based healthy plate education intervention. A quasi-experimental pre–post design without a control group was implemented among 63 students from grades IV to VI. The intervention integrated visual media, interactive instruction, and practical demonstrations based on the “My Plate” concept. Knowledge levels were assessed using structured pre-test and post-test instruments and analyzed using the Wilcoxon Signed-Rank Test. The results showed a substantial shift in knowledge distribution, with the proportion of students in the “good” category increasing from 23.8% to 71.4%. Statistical analysis revealed a significant difference between pre-test and post-test scores (Z = -5.543, p < 0.001), with a large effect size (r = 0.69). No participant experienced a decrease in score after the intervention. These findings indicate that school-based interactive nutrition education incorporating visual and experiential components can effectively enhance primary school students’ nutritional knowledge. Further longitudinal studies are recommended to assess the sustainability of behavioral changes.